A new class of high-entropy perovskite oxides. (1st January 2018) - Jiang, Sicong; Hu, Tao; Gild, Joshua; Zhou, Naixie; Nie, Jiuyuan; Qin, Mingde; Harrington, Tyler; Vecchio, Kenneth; Luo, Jian
Abstract: A new class of high-entropy perovskite oxides ( i.e., multiple-cation solid solutions with high configurational entropies) has been synthesized. Six of the 13 compositions examined, including Sr(Zr0.2 Sn0.2 Ti0.2 Hf0.2 Mn0.2 )O3, Sr(Zr0.2 Sn0.2 Ti0.2 Hf0.2 Nb0.2 )O3, Ba(Zr0.2 Sn0.2 Ti0.2 Hf0.2 Ce0.2 )O3, Ba(Zr0.2 Sn0.2 Ti0.2 Hf0.2 Y0.2 )O3 − x, Ba(Zr0.2 Sn0.2 Ti0.2 Hf0.2 Nb0.2 )O3 and (Sr0.5 Ba0.5 )(Zr0.2 Sn0.2 Ti0.2 Hf0.2 Nb0.2 )O3, can form homogeneous single solid-solution phases. Goldschmidt's tolerance factor, instead of cation-size difference, influences the formation and temperature-stability of single cubic perovskite solid solutions. This new class of multicomponent (high-entropy) perovskite solid solutions with distinct and highly-tunable chemistries can enable simultaneous tailoring of multiple properties and potentially lead to new functionality. Graphical abstract: The formation of a homogenous solid solution of perovskite Sr(Zr0.2 Sn0.2 Ti0.2 Hf0.2 Mn0.2 )O3, which is one example of the six high-entropy perovskite oxides synthesized in this study.